Extraskeletal Ewing’s sarcoma of the mediastinum: Case report - Caltavituro, Aldo; Buonaiuto, Roberto; Salomone, Fabio; Morra, Rocco; Pietroluongo, Erica; De Placido, Pietro; Tortora, Marianna; Peddio, Annarita; Picozzi, Fernanda; Ottaviano, Margaret; Marino, Mirella; De Placido, Sabino; et al. (Frontiers in Oncology, 2023)
Background Ewing sarcoma (ES) represents the second most common malignant bone tumor in children and young adults. ES is not a frequent finding in sites different from the skeletal. Common sites of appearance of ES are lower extremities, the pelvis, paravertebral spaces and head and neck. Primary extraskeletal ES located in the anterior mediastinum are very rare. These neoplasms should be discussed in specialized contests with a high volume of patients treated. Here, we present an uncommon mediastinal mass challenging in its characterization and management. Case description A thirty-year-old woman performed a thoracic CT scan for dyspnea and persistent cough. Imaging showed a solid mass of 14 x 11 cm involving the left thorax with mediastinal deviation to the right side. Patient underwent an en bloc resection of the mass. Initial histological examination was suggestive for B3 thymoma/thymic carcinoma. Patient was then referred to our rare tumor reference center where a histological review excluded the diagnosis of thymic/thymoma neoplasms meanwhile a third revision assessed a diagnosis of ES. Patient refused adjuvant chemotherapy due to her desire of maternity and radiation therapy was not indicated because surgery was performed too many months earlier. A close follow-up was considered. After a few months the patient relapsed and first line chemotherapy was proposed. She reached a complete response at the first evaluation maintained also at the end of the protocol. In order to consolidate the obtained response, high dose chemotherapy followed by autologous stem cell transplantation (HDCT/ASCT) was suggested and the patient agreed. Conclusions This case underlined that, potentially, ES can arise from any soft tissue site in the body, even in rare sites such as mediastinum. The evaluation of expert centers was critical to establish a correct diagnosis and therapeutic approach in this complex case. Taking into account the time lasting from the diagnosis and the aggressiveness of this kind of neoplasm, frequently relapsing, the patient after a multidisciplinary discussion was a candidate for a multimodal treatment.